Evaluation of a Reinforced Concrete Wall Macroscopic Model for Coupled Nonlinear Shear-Flexure Interaction Response - Joko Purnomo; Jimmy Chandra (Institute of Research and Community Outreach - Petra Christian University, 2018)
Reinforced concrete shear wall (RC wall) is an important element in tall buildings, which provides strength and stiffness against lateral loadings, e.g. earthquake and wind. Numerous researches have been conducted to study its nonlinear behavior via microscopic and macroscopic model. The later approach is currently being widely explored since it has many advantages compared to the preceding models. A well-known macroscopic model, namely Shear-Flexure-Interaction Multiple-Vertical-Line-Elements-Model (SFI-MVLEM) in the open source platform Open Sees, is capable of simulating the coupled nonlinear shear-flexure interaction response in the RC wall. This paper presents an evaluation to the applicability of SFI-MVLEM model to predict the coupled nonlinear shear-flexure behavior of RC wall specimens compared to experimental results in available literature. The analysis results show that the model is able to predict the behavior of RC wall considerably accurate in terms of hysteretic curves, cracking patterns, and contributions of shear and flexural displacement to total displacement.